2007
DOI: 10.1631/jzus.2007.b0626
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative localization and minimally invasive management of primary hyperparathyroidism concomitant with thyroid disease

Abstract: Abstract:The coexistence of thyroid diseases with primary hyperparathyroidism (PHPT) can present a challenge in the clinical diagnosis and management for these patients. This study aims to determine the frequency of coexisting thyroid gland lesions in a consecutive series patients with PHPT, and to analyze the clinical features, diagnosis and treatment of these patients. Twenty-two cases of a total of 52 PHPT patients who had synchronous thyroid and parathyroid pathology were surgically managed in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…The main diagnostic limitation of PTH-FNAB sampling is posed by a small and/or unclear target. All available techniques are sequentially justified in order to improve surgical outcome when thyroid abnormalities are concomitant (Zheng et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The main diagnostic limitation of PTH-FNAB sampling is posed by a small and/or unclear target. All available techniques are sequentially justified in order to improve surgical outcome when thyroid abnormalities are concomitant (Zheng et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Also, a limited preparation area allows a reduced risk of complications, which shortens the time of postoperative care and helps to lower the costs of treatment [10][11][12].…”
mentioning
confidence: 99%
“…Most of the studies claimed that preoperative localization was heavily influenced by coexistence of a nodular thyroid disorder. 7,9,[13][14][15][16][17] We also concluded on such an observation because of the significant difference between FNA-PTH-negative and FNA-PTH-positive groups for multinodularity (P = 0.01), but not for single nodules.…”
Section: Mibi Localizes Parathyroid Lesions In Patients With Php With Anmentioning
confidence: 75%
“…mm versus 13(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) mm in washout-negative group. The previous studies 10 reported a positive correlation between the size of lesion, PTH-FNAB and peripheral PTH values which we could not observe.…”
mentioning
confidence: 86%